Severe pulmonary tuberculosis complicating Ileocecal intussusception due to intestinal tuberculosis: a case report - Yamamoto Yoshihiro; Kakeya Hiroshi; Seki Masafumi; Izumikawa Koichi; Yanagihara Katsunori; Nakamura Shigeki; Miyazaki Yoshitugu; Suyama Naofumi; Kohno Shigeru (BMC, 2008)
Abstract Adult intussusception is a rare clinical entity that is most often caused by a tumor, such as a lipoma, adenoma, or malignant tumor. A case of adult intussusception due to intestinal tuberculosis of the ileocecal region is reported. There are few cases of intussusception due to intestinal tuberculosis.